The importance of citizenship responsibility for the young generation in the conservative anti-corruption movement - Sakban, Abdul; Budimansyah, Dasim; Darmawan, Cecep; Syaifullah (Universitas Negeri Yogyakarta, 2025)
The young generation plays a crucial role in combating corruption; however, their engagement is suboptimal due to insufficient ethical awareness regarding corruption issues and challenges in differentiating between corruption within governmental systems and public services. This research aims to investigate the civic responsibilities of the youth in the anti-corruption movement. The research method employed is qualitative, using an ethnographic approach. This study's findings indicate that civic responsibility manifests in two dimensions: citizen engagement and citizen participation in addressing and eliminating corruption within educational, social, legal, and religious contexts. The youth significantly contribute to the conservative anti-corruption movement by fostering and reinforcing moral, spiritual, cultural, and civic values within an environment that cultivates and shapes the attitudes and behaviours of active, creative, and innovative individuals in the battle against corruption. Consequently, it can be inferred that this conservative anti-corruption initiative aims to cultivate character and integrity among youths through extensive campaigns, promotions, counselling, and mentoring.